Breeding for sustainability: how reproductive biotechnologies can help buffalo farmers combat climate change - Pietro Sampaio Baruselli; Laís Ângelo de Abreu; Vanessa Romário de Paula; Sofía Albertini; Guilherme Felipe Ferreira dos Santos; Lígia Mattos Rebeis; Emanuelle Almeida Gricio; Nelcio A.T. de Carvalho; Otavio Bernardes (Revista Científica)
The global attention on enteric CH4 production in ruminants requires a response that involves collaboration between researchers and industry. Future generations of buffaloes will be characterized by better efficiency and fertility, which may reduce CH4 emission intensity. This goal will result from balanced multi-trait selection and the introduction of efficient reproductive and productive management. Currently, efficient reproductive programs using assisted reproductive technologies (ARTs) are available on buffalo farms. Our expanding knowledge of ovarian function during the buffalo estrous cycle has given new approaches for precisely synchronizing follicular development and ovulation to apply ARTs consistently. Synchronization protocols are designed to control both luteal and follicular function and permit fixed-time AI with high pregnancy rates during the breeding (autumn-winter) and non-breeding (spring-summer) seasons. Additionally, it allows the initiation of superstimulatory treatments at a self-appointed time, providing opportunities to superstimulate buffaloe donors associated with ovum pick-up (OPU) and in vitro embryo production (IVEP). Furthermore, it allows fixed-time embryo transfer in recipients, with high efficiency and no need for estrus detection. Thus, ARTs, such as AI and ET, are applied for buffalo’s targeted multiplication and dispersal with defined production and environmental credentials. Also, the urgency in moving to the next generation of buffaloes will increase the production of embryos from genomically defined prepubertal heifers. Using these biotechnologies will reduce generation interval and accelerate the rate of genetic improvement to buffalo, defined by better efficiency and fertility and lower CH4 emission. The challenge remains to communicate the importance of buffaloes for food security and the environment.